The pedigree analysis and prenatal diagnosis of Hong Kongαα Thalassemia and the sequence analysis of Hong Kongαα Allele. Issue 7 (18th May 2020) - Wang, Wenjuan; Zheng, Haiqing; Zeng, Dan; Jiang, Linbin; Yu, Donglan; Yang, Yuzhong; Feng, Qiao; Xia, Yang; Zhu, Chunjiang
Abstract: Background: Thalassemia is one of the most common monogenic hemolytic disorders in the world. Hong Kongαα ( HKαα ) thalassemia was initially found among the people of southern China. Because of the complexity of genetic changes in HKαα thalassemia, we lack a precise sequence analysis of the HKαα allele. Here we aim to detect the specific genotype and trace the law of inheritance of this rare genotype. Methods: We recruited an unprecedented huge pedigree containing 11 individuals carrying the HKαα thalassemia gene and 4 nongenetic‐related patients suffering from HKαα from south China. Regular hematological analysis and routine genetic screening were performed on the pedigree and two‐round nested PCR (polymerase chain reaction) for HKαα thalassemia were performed on each individual. The first‐generation gene sequencing was performed on six individuals, including four nongenetic‐related patients. Result: We found that five family members were positive for the HKαα allele. Patients Ⅱ‐2, Ⅲ‐1, and Ⅱ‐3 with only HKαα/‐‐ SEA or HKαα/‐α 4.2 presented with α‐thalassemia minor trait. Ⅰ‐1, the carrier of both HKαα/‐α 3.7 and β 41‐42 /β N, showed a typical β‐thalassemia trait. Fetus with genotype HKαα/‐α 4.2 alone was not likely to suffer from any deleterious effects after birth. The whole sequence of HKαα allele revealed that HKαα alleles in the six patients shared a high similarity, implying that all HKαα alleles are likely from the same ancestor. Moreover, pedigree and sequencing analyses demonstrated that the HKαα allele contained ααα anti4.2 mutation, ‐α 3.7 mutation, and a fragment from α‐ hemoglobin gene; thus, the composition and formation of HKαα allele was revealed. Finally, the high similarity and composition of HKαα alleles implies that once HK αα formed, ααα anti4.2 and ‐α 3.7 mutations tended to be a fusion gene and quite impossible to be inherited separately. Conclusion: The two‐round nested PCR is an effective method to detect HKαα allele . Besides, our study for the first time revealed the sequence of the HKαα allele, the evidence of the same ancestor with HKαα thalassemia and enriched the composition as well as the formation mechanism of HKαα allele, and immediately opened up novel potential diagnosis and prenatal counseling for HKαα thalassemia. Abstract : A rarely huge pedigree of HKαα thalassemia is reported and an effective prenatal counseling is offered to this family. Furthermore, αααanti4.2 detection assay is once again proposed to screen for HKαα allele in the patients positive for – α3.7 mutation by our current studies. The relationship between genotypes and phenotypes of HKαα thalassemia was also analyzed here for clinicians to avoid the possible misdiagnosis. More importantly, our study for the first time reported the sequence of the HKαα allele, the evidence of the same ancestor with HKαα thalassemia and enriched the composition as well as the formation mechanism of HKαα allele，and immediately opened up novel potential diagnosis and prenatal counseling for HKαα thalassemia.